2014
DOI: 10.1007/s11661-014-2483-y
|View full text |Cite
|
Sign up to set email alerts
|

Serration Dynamics in a Zr-Based Bulk Metallic Glass

Abstract: Intermittent or serrated plastic flows have been widely observed in irreversible deformation through shear banding in bulk metallic glasses (BMGs). The strain-rate-dependent plasticity under uniaxial compression at 2 9 10 À3 , 2 9 10 À4 , and 2 9 10 À5 s À1 in a Zr-based BMG is investigated. Serration events have a typical time scale at a relatively higher strain rate (2 9 10 À3 s À1 ), while at lower strain rates, there is a lack of typical time scale. During serrations, the stress is falling rapidly, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…It is obvious that the yielding strengths are almost the same value of 1650 MPa, and the compressive plasticity keeps similar values about ~6% at different strain rates. The repeating cycles of a sudden stress drop are followed by reloading elastically, which accord with the previous results [23][24][25]. In order to eliminate the machine vibration error, any serration event with a stress fluctuation less than 5 MPa in jerky flows is excluded in the present statistical analysis.…”
Section: Resultssupporting
confidence: 81%
“…It is obvious that the yielding strengths are almost the same value of 1650 MPa, and the compressive plasticity keeps similar values about ~6% at different strain rates. The repeating cycles of a sudden stress drop are followed by reloading elastically, which accord with the previous results [23][24][25]. In order to eliminate the machine vibration error, any serration event with a stress fluctuation less than 5 MPa in jerky flows is excluded in the present statistical analysis.…”
Section: Resultssupporting
confidence: 81%
“…Such results indicate that a pure SOC behaviour might not be the only option for MGs plasticity. Some other studies also have shown that the plasticity could also be achieved with a serration pattern in peak distribution [17,18]. Some studies suggest that the shear band dynamics in plastic MGs could also be understood by a tuned criticality behaviour instead of the SOC behaviour [16].…”
Section: Serration Pattern and Shear Band Dynamicsmentioning
confidence: 97%
“…Some statistics studies reveal that the shear bands follow a self-organised critical (SOC) behaviour or chaotic KEYWORD Metallic glass; shear band; plasticity; serration ARTICLE HISTORY behaviour in MGs with different plasticity, where the serration pattern falls in a power law distribution or peak distribution [10,11,15]. However, there are also contradictory reports showing different serration patterns and shear band dynamics in plastic MGs [16][17][18]. Then, it is important to reveal the origin of the different plasticity in MGs, and the relationship among serration pattern, shear band dynamics and plasticity of MGs.…”
Section: Introductionmentioning
confidence: 99%
“…More comprehensive mechanisms are expected. For example, very recently, we have unveiled an exponential decay of shearing stresses with the time or strain during serrations in BMGs [253,262]. The flow stresses with the time satisfy the following relation: c is the heat capacity, T r is room temperature, T g is the glass-transition temperature, E is the Young's modulus of BMGs, and a is the aspect ratio of the tested samples.…”
Section: Serration Kineticsmentioning
confidence: 99%